A Proposed Implementation of Final Income Tax on Cashback - Sekar Mayangsari; Hidayanti, Winda; Estiani, Oktaviasari Wanitaningrum (Universitas Pendidikan Ganesha, 2025)
This research aims to evaluate the imposition of income tax (Pajak Penghasilan—PPh) on cashback transactions based on the hard-to-tax theory, and explore the implementation of final income tax (Pajak Penghasilan Final—PPh final) as an alternative taxation mechanism for cashback transactions, aligned with basic taxation principles and the hard-to-tax theory. A qualitative case study design was employed. This involved in-depth interviews with an Account Representative from the Directorate General of Taxes, a taxation academic, and several active e-commerce users. The findings confirm that cashback transactions fall within the hard-to-tax (HTT) sector, thereby justifying the proposal of a final income tax as a more administratively feasible and equitable solution. To ensure fairness in tax collection, it is important to consider taxpayers’ payment capacity, applicable tax rates, and the involvement of third parties—such as platforms—in tax withholding responsibilities. As a reference, the study benchmarks the application of final income tax on lottery prizes, while proposing necessary contextual adjustments for the digital economy. The recommended policy is expected to safeguard potential state revenue from cashback incentives without disrupting the continued growth of Indonesia’s e-commerce sector or its broader digital economy ecosystem.